Mapping of the use and coverage of the soil in mesoregions of the State of Rondônia (Research, Society and Development, 2020)
Due to its extension, the Amazon region is composed of an intricate mosaic of environments, defined not only by the heterogeneity of its ecosystems, but also by the process of occupation and development. Based on this aspect, the growth of populations and the expansion of urban areas worldwide have increased the use and defined changes in land cover. Thus, the objective of this work was to carry out the mapping of land use and cover in the surroundings of Rondônia. The study was carried out in the municipalities of Corumbiara, Chupinguaia and Cerejeiras, these located in the south of the state of Rondônia, where the images used for the analyzes were acquired on the platform of the General Image Division (GID) of the National Institute for Space Research (INPE) , 1990 images of the TM (Thematic Mapper) sensor on board the Landsat-5 satellite, and 2017 of the OLI sensor (Operational land imager) on the Landsat-8 satellite, characterized by a spatial resolution of 30 meters and temporal resolution of 16 days. The results showed an area with significant deforestation, where approximately 2/4 of the total territory of the municipalities had their original vegetation removed and, thus, shows an irregularity when compared with the environmental legislation (Law nº 12.651 / 2012).